Automatic detection of student off-task behavior while using an intelligent tutor for algebra - Bate, Allan Edgar C. (Philippine computing journal)
As more and more modern classroom use Intelligent Tutoring Systems, it becomes imperative for our educators to determine whether these systems are being used properly, or whether students engage in off-task behavior...